HEALING OR HURTING: DEVELOPMENT OF HIGHWAY PUBLIC TRANSPORTATION TECHNOLOGY - Nurul Qamar; Aan Aswari (Jurnal Dinamika Hukum, 2018)
A collaboration of information technology with public transportation has brought an impact on the improvement of public service in terms of public transportation online due to the government incapability to provide good service. This study illustrates that there is an expectation to be built by the concept of law namely through a legal approach that serves as a cure from the perceived failure resulting from the lack of law in accommodating the needs of society for providing maximum service on public transport. Meanwhile, the emergence of regulations that provide the legality of an action in fact exacerbates the wound. This paper is not intended to reject the collaboration of technology. However, it may fail to cope with human needs but not in conjunction with new technology. In conclusion, the law should easily materialize its goal of public transportation innovation and becomes a healer from previous product failures. Keywords: technology, transportation, online, street